Intellectualization of vacuum circuit breakers in medium- and high-voltage networks - Semenov, A.; Pavlenko, V.; Skrypnyk, V. (Energy and Automation, 2026)
The relevance of the study is обусловлена the need to improve the reliability and safety of switching equipment in medium- and high-voltage networks under conditions of substation digitalization and the transition to condition-based maintenance. The aim of the study is to substantiate the feasibility of using vacuum circuit breakers in combination with digital monitoring systems and to develop an approach to the integrated assessment of their technical condition. To achieve this aim, analytical, comparative, and structural-functional research methods were applied; scientific sources and the provisions of IEC 62271-100 and IEC 61850-3 standards were analyzed. The paper summarizes the advantages of vacuum circuit breakers in comparison with oil, air, and SF6 analogues and identifies the most informative diagnostic parameters, namely operating time, contact resistance, local overheating, drive vibration condition, and consumed switching life. An integrated technical condition index is proposed, combining electrical, thermal, mechanical, temporal, and resource-related indicators and enabling the determination of equipment maintenance priorities. It has been established that the integration of vacuum circuit breakers with digital controllers, sensors, and the SCADA level based on IEC 61850 increases the informativeness of monitoring, facilitates early detection of degradation processes, and creates prerequisites for predictive maintenance. The practical significance of the results lies in the possibility of their application in the modernization of switchgear at industrial and agro-industrial enterprises. Recieved: 23.02.2026. Recieved: 15.05.2026. Accepted: 22.06.2026